Determinants of Perceived Own Risk for Developing Dementia and the Perception That Memory Deterioration Is Preventable. Findings From the General Adult Population in Germany - Hajek, André; König, Hans-Helmut (Frontiers in Medicine, 2020)
Objective: To identify among the general population the determinants of (1) perceived own risk for developing dementia and (2) the perception that memory deterioration is preventable. Methods: For this study, cross-sectional data were taken from the German Socio-Economic Panel (innovation sample, year 2012) which is a population-based, longitudinal study of German households. 1,542 individuals were included in our analytical sample. Results: Multiple linear regressions showed that an increased perceived own risk for developing dementia was associated with younger age, higher education, poor self-rated health, an increased number of chronic diseases, and an increased agreement that a diagnosis of dementia would ruin their life. An increased perceived modifiability of memory deterioration was associated with higher education, and not being employed, but not health-related variables. Conclusion: Several determinants of the perceived own risk for developing dementia and the perceived modifiability of memory deterioration have been identified. Addressing modifiable factors may be beneficial for changing these outcome measures.